Ecological interactions between Antarctic krill (Euphausia superba) and baleen whales in the South Sandwich Islands region – Exploring predator-prey biomass ratios. (November 2022) - Baines, Mick; Jackson, Jennifer A.; Fielding, Sophie; Warwick-Evans, Vicky; Reichelt, Maren; Lacey, Claire; Pinder, Simon; Trathan, Philip N.
Abstract: Following the cessation of whaling, the southwest Atlantic humpback whale ( Megaptera novaeangliae ) population is thought to be close to pre-exploitation size, reversing 20th century changes in abundance. Using a model-based approach applied to concurrently collected data on baleen whale abundance and Antarctic krill ( Euphausia superba ) biomass in the South Sandwich Islands (SSI) region, we explore ecological interactions between these taxa. Krill biomass and baleen whale density were highest to the north and northeast of the SSI, where the Antarctic Circumpolar Current (ACC) is deflected around the island chain. Humpback whale density was elevated at locations of krill biomass density >150 gm -2 . Krill consumption by baleen whales was estimated at 19–29% of the available krill standing stock. We used historic whaling data to confirm the plausibility of these consumption rates and found evidence of rapid weight gain in humpback whales, such that blubber depleted during the breeding season could be restored in a much shorter period than previously assumed. Little is known about krill replenishment rates in the flow of the ACC, or about niche separation between recovering baleen whale populations; both factors may affect species carrying capacities and further monitoring will be required to inform the management of human activities in the region. Highlights: Krill biomass density distribution was modelled using a two-stage Maxent/GLM process. Humpback whale abundance and distribution was modelled using a GAM. Whales consume 19–29% of available krill in the South Sandwich Islands region. On southern feeding grounds humpback whales can rapidly restore depleted blubber. Future studies on rates of krill transport in oceanographic currents will be important.